A study to determine the motor proficiency of children between the ages of six and ten years diagnosed with ADHD in the Cape Metropole - Statham, S. B. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScPhysio)--Stellenbosch University, 2004